Artificial Intelligence and Enhancing Accounting Practices in Selected African Countries - Olaoye, Ayoola Azeez (Universitas Kristen Maranatha, 2025)
Purpose – As the firms in Africa strive to modernize and compete globally, Artificial Intelligence adoption becomes imperative for the transformation of their accounting practices, particularly in Nigeria, South Africa, and Kenya. The aim of this study is therefore to examine the role of AI in improving accounting processes and operational efficiency in selected multinational companies in three under-studied countries. Design/methodology/approach – The study used a quantitative research design through questionnaires distributed to Chief Financial Officers/Accountants in 30 multinational firms with a documented history of AI adoption. The data were analyzed using statistical tools such as content analysis, figures, and measures of central tendency to explore AI's impact. Findings – The study’s results disclosed a significant improvement in accounting practices due to AI adoption with South Africa leading in implementation, followed by Kenya and Nigeria. The result also revealed long-term benefits, including reduced human error, streamlined processes, and improved financial reporting timelines, particularly in South African firms. The study concluded that AI adoption is essential for firms seeking to enhance operational efficiency Research limitations/implications – This study's scientific novelty is the comparative analysis of AI adoption across three African economies, which provides fresh insights into how AI-driven innovations improve organizational processes and efficiency. Its relevance stems from the significance of AI in optimizing accounting practices, which boosts the competitiveness of businesses in Sub-Saharan Africa. Keywords: Artificial Intelligence, Enhancing Accounting Practices, Listed Multinational Companies, Sub-Saharan Africa